Prikaz raziskav bakterije Helicobacter pylori v Splošni bolnišnici Maribor od leta 1988 do 2005 - Reberšek Gorišek, Jelka (Zdravniški vestnik, 2006)
Background. The discovery of the bacterium Helicobacter (H) pylori in biopsy specimens from the gastric mucosa and the confirmation of its key role in the pathogenesis of duodenal and gastric ulcer disease, and gastritis, its significant role in mucosa associated lymphoid tissue (MALT) lymphoma and in the occurrence of gastric cancer also offered the possibility of causal treatment of these diseases with antimicrobial agents. The aim of antimicrobial treatment is the eradication of H. pylori, the decrease of recurrences and lessening the risk of gastric cancer diseases. H. pylori infection is treated with a combination of several antimicrobials. The human stomach is a natural reservoir of H. pylori. In the prevalence of H. pylori infection, patient age, socio-economic status, living and sanitary conditions can play an important role. Determination of serum IgG and IgA antibodies against H. pylori and detection of the antigen in the feces of asymptomatic patients is important for epidemiologic studies. Patients and methods. The study included patients with chronic gastritis and with recurrence of duodenal and gastric ulcer disease referred routinely to Maribor Teaching Hospital (MTH) while the study on the identification of serum antibodies against H. pylori and of antigen in feces included asymptomatic patients. For confirmation of H. pylori in biopsy specimens of the gastric mucosa we used the histologic method, culture, the urease test and the nested polymerase chain reaction (nested PCR) method. The latter was also used for dental plaque smears. Antimicrobial treatment with the aim of eradicating H. pylori was carried out in three studies comparing two groups of patients: The first group always received ranitidine - 2 x 150 mg over 3 weeks in the first study and over 8 weeks in the two further studies, with an addition of antacids if needed. The second group received ranitidine 2 x 150 mg + erythromycin 4 x 500 mg for one week in the first study, ranitidine 2 x 150 mg + colloidal bismuth subcitrate (CBS) 2 x 240 mg over 4 weeks in the second study, and CBS 4 x 120 mg + amoxycillin 4 x 500 mg + metronidazole 4 x 500 mg over two weeks in the third study. With the latex agglutination and with the enzyme immune system (Virion-Serion) we identified IgG and IgA antibodies against H. pylori in serum, and antigen in feces (HpSA - Meridian). In protocols of epidemiologic characteristics of H. pylori infection we collected and analyzed the data regarding patient age and gender, living and sanitary conditions, socio-economic status and the education level. Results. The studies showed that H. pylori was most frequently present in ulcer disease of duodenum and stomach. The success of antimicrobial treatment and eradication of H. pylori with ranitidine and erythromycin over one week was 11.1 %, with the combination of ranitidine and CBS over four weeks 19.04 %, with the triple combination therapy with CBS + amoxycillin + metronidazole over two weeks 92 %. In dental plaque, H. pylori was confirmed in 16.6 %. Middle age, poor or medium living conditions and economic status, and primary to secondary education were all identified as possible risk factors for H. pylori infection. In asymptomatic patients we confirmed IgG antibodies against H. pylori in serum in 26/34, in 1/34 they were borderline positive, and negative in 7/34 patients. IgA antibodies were present in 17/34, in 6/34 they were borderline positive, and negative in 11/34. Antigen in feces was positive in 10/33 patients, negative in 23/33. Serum IgG and IgA antibodies and antigen in feces were confirmed in 8/23 patients. Conclusions. Our studies resulted in the beginning of H. pylori detection in MTH patients with gastritis and ulcer disease, and in the ascertainment that H. pylori was most frequently present in ulcer disease of stomach and duodenum. For the confirmation of H. pylori, the histologic method, culture and the urease test were introduced into routine clinical practice of MTH. Causal treatment of gastritis and ulcer disease with antimicrobials was introduced, and the success of H. pylori eradication and the decrease of recurrences was followed. We found that antimicrobial sensitivity in vitro did not warrant clinical success - a statement proved by the results of treatment with erythromycin. The effect of monotherapy was also insufficient. The hypothesis that dental plaque could be a significant reservoir of H. pylori infection was not confirmed. The nested PCR method for proof of H. pylori in gastric mucosa biopsy specimens and dental plaque smears is a rapid and reliable diagnostic method. The analysis of epidemiologic characteristics showed that risk factors for the occurrence of H. pylori infection are middle age, poor or medium living conditions and socio-economic status, and primary to secondary education. In asymptomatic patients we proved the presence of IgG and IgA antibodies, and of antigen in feces.
Keywords: bacteria; bakterije; diagnosis; Diagnostika; Drug Therapy; Epidemiologija; epidemiology; Gastritis; Helicobacter pylori; microbiology; Mikrobiologija; Peptic Ulcer; Peptični ulkus; therapy; ulkus; zdravljenje; Zdravljenje z zdravili